Clinical Value and Potential Mechanisms of Oxysterol-Binding Protein Like 3 (OSBPL3) in Human Tumors - Hao, Na; Zhou, Yudong; Li, Yijun; Zhang, Huimin; Wang, Bin; Liu, Xiaona; Ren, Yu; He, Jianjun; Zhou, Can; Tang, Xiaojiang (Frontiers in Molecular Biosciences, 2021)
Cancer remains one of the top culprits causing disease-related deaths. A lack of effective multi-cancer therapeutic targets has limited the prolongation of cancer patients’ survival. Therefore, it is important to explore novel oncogenic genes or versatile targets and perform a comprehensive analysis to assess their roles in the process of tumorigenesis. OSBPL3 protein is an intracellular lipid receptor of the oxysterol-binding protein superfamily, which participates in some pathological and physiological processes in tumor progression. However, its clinical roles and potential mechanisms in cancers remain unknown. Thus, we aimed to systematic explore the potential oncogenic roles of OSBPL3 across thirty-three tumors using multiple web-based and publicly available tools, including the Cancer Genome Atlas, Gene Expression Omnibus, Genotype-Tissue Expression, cBioPortal, and Human Protein Atlas database. OSBPL3 is highly expressed in major subtypes of cancers, distinctly associated with the prognosis of tumor patients. We observed X676_splice/V676G alteration in the oxysterol domain and frequent mutations of OSBPL3 involve cell survival in skin cutaneous melanoma. We also first presented that the expression of OSBPL3 was associated with tumor mutational burden (TMB) in nine cancer types. Additionally, OSBPL3 shows an enhanced phosphorylation level at S426, S251, and S273 loci within the pleckstrin homology domain in multiple tumors, such as breast cancer or lung adenocarcinoma. And OSBPL3 expression was associated with active immune cells (CD8+ T cells) and cancer-associated fibroblasts in breast cancer, colon adenocarcinoma, and kidney renal clear cell carcinoma and immune checkpoint genes in more than 30 tumors, but weakly associated with immune suppressive cells (myeloid-derived suppressor cells, T regulatory cells). Moreover, protein processing and mRNA metabolic signaling pathways were involved in the functional mechanisms of OSBPL3. Our study first demonstrated that a novel agent OSBPL3 plays an important role in tumorigenesis from the perspective of publicly available databases and clinical tumor samples in various cancers, which comprehensively provide insights into its biological functions and may be helpful for further investigation.